Persepsi Masyarakat Indonesia Terhadap Peran Apoteker Komunitas Dalam Meningkatkan Kesehatan Seksual Dan Reproduksi - Putra, Mikha Adyatama; Soegiantoro, Didiek Hardiyanto; Kristariyanto, Yosua Adi; Raditya, Rakta (Jurnal Kesehatan Ilmiah Aufa Royhan, 2026)
Community pharmacists play an important role and contribute to improving sexual and reproductive health in the community, but understanding of the role of pharmacists has not been clearly described. This study aims to describe the Indonesian community's perception of the role of community pharmacists in improving sexual and reproductive health based on the frequency of visits to health facilities and pharmacies. The study used a quantitative descriptive design with a cross-sectional approach. Based on the Cochran formula, 100 samples were selected, consisting of Indonesians aged >18 years. Data were obtained from a questionnaire distributed via the Google Forms online platform. The questionnaire met the construct validity and reliability tests. The relationship between public perception based on the frequency of visits to health facilities and pharmacies was analysed using the chi-square test. The results showed that the majority of respondents were aged 18-24 years (41 people). A total of 63 respondents rarely visited health facilities, while 47 respondents rarely visited pharmacies. The results of the Pearson chi-square test showed no relationship between perceptions and frequency of visits to health facilities (p-value = 0.392) or pharmacies (p-value = 0.201). It is recommended that community pharmacists strengthen sexual and reproductive health services and collaborate with educational institutions and other communities.